Identifying factors explaining practice variation in secondary stroke prevention in primary care: a cohort study based on all patients with ischaemic stroke in the Stockholm region. Issue 11 (21st November 2022) - Wolf, Maria; Hasselström, Jakob K; Carlsson, Axel; Euler, Mia von; Hasselström, Jan
Abstract : Objectives: The aim of this study was to describe the practice variation in dispensation of secondary stroke preventive drugs among patients at different primary care centres (PCCs) in Stockholm region and to identify factors that may explain the variation. Design: Cohort study using administrative data from the Stockholm region. Setting: Stockholm Health Care Region, Sweden, serving a population of 2.3 million inhabitants, hospital and PCC data. Participants: All patients (n=9761) with ischaemic stroke treated in hospital from 1 July 2009 to 30 June 2014 were included. Of these, 7562 patients registered with 187 PCCs were analysed. Exclusion criteria were; deceased patients, age <18, haemorrhagic stroke and/or switching PCC. Primary and secondary outcome measures: As primary outcome the impact of PCC organisation variables and patient characteristics on the dispensation of statins, antiplatelets, antihypertensives and anticoagulants were analysed. Secondarily, the unadjusted practice variation of preventive drug dispensation of 187 PCCs is described. Results: There was up to fourfold practice variation in dispensation of all secondary preventive drugs. Factors associated with a lower level of dispensed statins were privately run PCCs (OR 0.91 (95% CI 0.82 to 1.00)) and the patient being woman. Increased statin use was associated with a higher number of specialists in family medicine (OR 1.03 (95% CI 1.01 to 1.05)) and a higher proportion of patients registered with a specific physician (OR 1.37 (95% CI 1.11 to 1.68)). Women had on average a lower number of dispensed antihypertensives. Conclusions: A high practice variation for dispensation of all secondary preventive drugs was observed. Patient and PCC level factors indicating good continuity of care and high level of general practitioner education were associated with higher use of statins. Findings are of importance to policymakers as well as individual providers of care, and more research and actions are needed to minimise inequality in healthcare.